Iliac crest bone graft donor site hernia: not so uncommon. (12th June 2013) - Prabhu, Raghunath; Kumar, Nawin; Shenoy, Rajgopal
Abstract : A 73-year-old man, who had undergone fracture fixation of humerus with LCP plating and bone grafting, presented again with a peri-implant fracture after 1 year. A repeat surgery was contemplated and replating was performed with tricortical bone graft harvested from the iliac crest. In the postoperative period the patient developed a tender swelling at the graft site with nausea and abdominal discomfort. It was managed conservatively thinking it to be a haematoma at the graft site. In the following 2 days his symptoms worsened. A CT abdomen showed the herniation of caecum from the bone graft donor site with obstruction. The patient was taken up for emergency surgical repair, the caecum was reduced and polypropylene mesh hernioplasty was performed. The patient recovered well without recurrence in the follow-up period. Iliac crest bone graft site hernia is not so uncommon and care has to be taken while harvesting.